EFEKTIVITAS PEMANFAATAN RUANG KELAS SEBAGAI SARANA PERKULIAHAN - Murib, Barson Robert; Supriyanto, Achmad; Sunandar, Asep (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
the purpose of this study was to (1) determine the level of effectiveness of the use of lecture rooms for Education Administration students in each semester course in the 2018/2019 academic year; (2) knowing the level of effectiveness of the use of lecture rooms for Education Administration students in the classes of 2016, 2017 and 2018 in the even semester of the 2018/2019 academic year; and (3) knowing the level of effectiveness of the use of lecture halls for all Education Administration students in the even semester of the 2018/2019 academic year. The research method used is descriptive research with quantitative research types. The data analysis technique used is descriptive analysis. The results of the study are (1) the level of effectiveness of the use of lecture rooms for Education Administration students in each semester course in the 2018/2019 academic year including the high category; (2) the level of effectiveness of the use of lecture rooms for the 2016, 2017 and 2018 Education Administration students in the even semester of the 2018/2019 academic year is also in high category; (3) the level of effectiveness of the use of lecture halls for all Education Administration students in the even semester of the 2018/2019 academic year is also in the high category.